Tingkat Kepuasan Gen-Z yang menjadi Pengunjung Perpustakaan Daerah Kota Serang - Sisca Dwi Aprilia; Noerma Kurnia Fajarwati; Meiby Zulfikar; Rizqi Fitrianti; Arfian Suryasuciramdhan (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the satisfaction level of Generation Z visitors at the Serang City Regional Library using Expectation Confirmation Theory (ECT). This theory explains that satisfaction is formed when the actual service meets or exceeds user expectations. The research employed a descriptive quantitative approach with a survey technique, involving 89 respondents aged 17–28 years, selected purposively. The data were collected using a questionnaire with a 1–4 Likert scale and analyzed univariately. The results show that the majority of Generation Z visitors are satisfied with the library services, with 85.4% expressing satisfaction, while 14.6% expressed dissatisfaction. The factors contributing the most to satisfaction were staff friendliness (58.4% reported being very satisfied), room comfort (59.6% reported being very satisfied), and the availability of basic facilities such as tables, chairs, and adequate lighting. However, dissatisfaction mainly stemmed from digital facilities. About 45% of respondents stated that the Wi-Fi connection was unstable, disrupting online information access. Additionally, 60% of respondents felt that the collection of the latest books was still limited, failing to meet the academic and current trends of Generation Z. These findings highlight the importance of improving digital services, enhancing internet network quality, and expanding the collection of up-to-date and popular books. Furthermore, staff competence in digital literacy needs to be enhanced to support the increasing digital needs of users. With these measures, the library is expected to not only maintain visitor satisfaction but also improve its relevance and loyalty in the digital era.